2014
DOI: 10.1186/1471-2407-14-369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel driver mutations of the discoidin domain receptor 2 (DDR2) gene in squamous cell lung cancer of Chinese patients

Abstract: BackgroundAlthough many of the recently approved genomically targeted therapies have improved outcomes for patients in non–small-cell lung cancer (NSCLC) with lung adenocarcinoma, little is known about the genomic alterations that drive lung squamous cell cancer (SCC) and development of effective targeted therapies in lung SCC is a promising area to be further investigated. Discoidin domain receptor 2 (DDR2), is a novel receptor tyrosine kinases that respond to several collagens and involved in tissue repair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…The initial study concluded that gain of functions mutations in DDR2 are oncogenic and provided the first targetable mutations in lung SCC [116] and hence caused much excitement in the field. However, the study did not address the contribution of wild-type DDR2 to oncogenesis, and while several more recent studies have confirmed the occurrence of DDR2 mutations in different patient populations [122][123][124], it is far from clear whether the mutations are indeed oncogenic and their roles in lung SCC cell signalling are undefined [125]. Notably, in other studies, some of the 'oncogenic' DDR2 mutants either seemed to play tumour suppressive functions [101], or did not contribute to cell proliferation in lung SCC cell lines [126].…”
Section: Ddrs and Cancermentioning
confidence: 99%
“…The initial study concluded that gain of functions mutations in DDR2 are oncogenic and provided the first targetable mutations in lung SCC [116] and hence caused much excitement in the field. However, the study did not address the contribution of wild-type DDR2 to oncogenesis, and while several more recent studies have confirmed the occurrence of DDR2 mutations in different patient populations [122][123][124], it is far from clear whether the mutations are indeed oncogenic and their roles in lung SCC cell signalling are undefined [125]. Notably, in other studies, some of the 'oncogenic' DDR2 mutants either seemed to play tumour suppressive functions [101], or did not contribute to cell proliferation in lung SCC cell lines [126].…”
Section: Ddrs and Cancermentioning
confidence: 99%
“…85,87 However, a range of DDR2 mutations have been identified, not all of which are definitely proven to be oncogenic. 87,88 To date, clinical trials of agents targeting DDR2 have been hampered by excessive toxicity, especially in patients with sqCLC. 89 Lack of efficacy has also been noted.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Of the two members of this small family, DDR1 is expressed in tumor cells of epithelial origin and DDR2 in tumor-associated stroma (37). In addition, DDR2 is mutated in squamous cell cancer (4.4%) (38) and in lung AD (2-5%) (29), whereas DDR1 overexpression is associated with poor prognosis in NSCLC (39,40). Interestingly, partial responses have been achieved using combinatorial therapies with dasatinib, a multitarget tyrosine kinase inhibitor that also blocks DDR2 (41).…”
Section: Dissemination Of Cancer Cells and Homing To Bone Tissuesmentioning
confidence: 99%